Superoxide-producing thermostable complex from plant foods: isolation, purification and properties - Simonyan, R. M.; Simonyan, G. M.; Alexanyan, A. S.; Babayan, M. A.; Alexanyan, S. S.; Simonyan, M. A. (Հայաստանի ԳԱԱ «Գիտություն» հրատ.)
From Armenian plant food – tomato (Solanum lycopersicum esculentum), carrot (Daucus carota subsp. sativus), green bean (Phaseolus vulgaris) and potato (Solanum tuberosum), the isoforms of superoxide (О2) producing complexes between NADPH containing protein component (NPC) and Fe(III) – NPC-Fe(III), were isolated and purified for the first time. At the same time, the fractionation of these complexes at pH 9,5 and 4,8 were carried out [1]. The isoforms of NPC-Nox are high thermostable biosystems (up to 100oC). The immediately mechanism of the production of О2 by these complexes, due to the transfer of the electron from NPC to the Fe(III), then to О2 for its reduction up to О2 was conditioned. As a substrate for NPC-Fe(III) is not free NADPH, but NADPH is connected with the protein component (PC). The forms of optical absorption spectra of these complexes in visible region essentially were differed, although, in UV region the characteristic for the proteins maximal optical absorption at 260-280 nm were observed. The higher specific content (mg/g) for complexes from tomato, than from carrot, green bean and potato were observed. The direct proportional dependence between the content of the NADPH in the composition of NPC and stationary concentration of produced О2 in homogenous phase (in solution) and gas phase were presented. The isolated NPC from indicated above complexes, at the expense of NADPH, only the reductive (antioxidant) effect was indicated and was activated the NADPH oxidase (Nox) in vitro, in particular from erythrocytes membranes (ЕМ) аnd leukocytes membranes (LM). By the blowing of the slightly opalescent aqueous solutions of these complexes with oxygen the gas phase О2 were produced, which were transferred oxygen through the silicone or glass tubes. Առաջին անգամ բուսական ծագման մթերքներից (լոլիկ, գազար, կանաչ լոբի և կարտոֆիլ) անջատվել և մաքրվել են սուպերօքսիդ (О2)-գոյացնող կոմպլեքսների իզոձևեր՝ NADPH, պարունակող սպիտակուցային բաղադրամասի (ՆՍԲ) և Fe(III)-ի միջև՝ ՆՍԲ-Fe(III): Ընդ որում իրականացվել է այդ կոմպլեքսների ֆրակցիոնացում pH 9,5-ում և pH 4,8-ում [1]. ՆՍԲ-Fe(III)-ի իզոձևերը համարվում են ջերմակայուն (մինչև 100оС) կենսահամակարգեր: Որոշված է այդ կոմպլեքսներով О2 գոյացման անմիջական մեխանիզմ, ինչը պայմանավորված է էլեկտրոնի փոխանցմամբ ՆՍԲ-ից Fe(III)-ին, ապա О2-ին, վերականգնելով այն մինչև О2: Որպես ՆՍԲ-Fe(III)-ի սուբստրատ համարվում է ոչ թե ազատ, այլ սպիտակուցային բաղադրամասի (ՍԲ) հետ կապված NADPH-ը: Այս կոմպլեքսների օպտիկական կլանման սպեկտրների ձևերը տեսանելի մարզում էականորեն տարբերվում են, չնայած ՈւՄ մարզում առկա են սպիտակուցներին բնորոշ մաքսիմալ օպտիկական կլանումներ 260-280 նմ-ում: Այդ կոմպլեքսների տեսակարար պարունակությունը (մգ/գ) բարձր է լոլիկի, ապա գազարի, կանաչ լոբու և կարտոֆիլի մեջ: Դիտվում է ուղիղ համեմատական կախվածություն ՆՍԲ-ի կազմում գտնվող NADPH-ի և գոյացող О2-ի ստացիոնար կոնցենտրացիայի միջև, հեղուկ (լուծույթում) ֆազում և գազ ֆազում: Վերոհիշյալ կոմպլեքսներից առանձնացված լեյկոցիտների ՆՍԲ-ն, շնորհիվ NADPH-ի, ցուցաբերում է վերականգնիչ (հակաօքսիդանտային) ազդեցություն և ակտիվացնում NADPH-օքսիդազը (Nox), մասնավորապես անջատված էրիթրոցիտների թաղանթներից (ԷԹ և ԼԹ) in vitro: Այդ կոմպլեքսների թույլ օպալեսցենցվող ջրային լուծույթի մեջ թթվածին փչելիս գոյանում են գազ ֆազային О2-ներ, որոնք մոլեկուլային թթվածնի հետ տեղափոխվում են սիլիկոնային կամ ապակյա խողովակով: Впервые из пищевых продуктов растительного происхождения (помидоры, морковь, зеленая фасоль и картофель) выделены и очищены изоформы супероксид (О2)-продуци-рующего комплекса между NADPH содержащим белковым компонентом (НБК) и Fe(III) – НБК-Fe(III). При этом было осуществлено фракционирование этих комплексов при pH 9,5 и pH 4,8 [1]. Изоформы НБК-Fe(III) являются термостабильными (до 1000С) биосистемами. Определен непосредственный механизм продуцирования О2 этими комплексами, который обусловлен передачей электрона от НБК к Fe(III), далее к О2, восстанавливая его до О2. Как субстрат фермента НБК-Fe(III) является не свободная, а связанная с белковым компонентом (БК) NADPH. Формы оптических спектров поглощения этих комплексов в видимой области существенно отличаются, хотя в УФ области имеются характерные для белков максимальные оптические поглощения при 260-280 нм. Удельное содержание (мг/г) этих комплексов выше в помидорах, далее в моркови, зеленой фасоли и картофеле. Наблюдается прямопропорциональная зависимость между содержанием NADPH в составе НБК и стационарной концентрацией продуцируемых О2 в жидкой фазе (в растворе) и газ фазе. Отделенный от приведенных комплексов НБК, за счет NADPH, оказывает только восстановительный (антиоксидантный) эффект и активирует NADPH оксидазу (Nox) in vitro, в частности, выделенные из мембран эритроцитов (ЕМ) и лейкоцитов (ЛМ). При продувании слабоопалесцирующего водного раствора этих комплексов кислородом продуцируются газ фазные О2, которые транспортируются с молекулярным кислородом посредством силиконовой или стеклянной трубок.
Keywords: Biology